Developing Halal Village Tourism Through Asset Community In Setanggor, Lombok Tengah - Mahardika, Fajar; Indrawati, Indrawati (JURNAL AT-TURAS, 2021)
Overcoming poverty problem constitutes a part of da’wah bil hal. Moreover, it is a main problem experienced by Moslems in Indonesia. To overcome the problem, the governor of Nusa Tenggara Barat TGB. Muhammad Zainul Majdi pionered Halal Tourist Village through his Governor rule no. 51/2016. The term of Halal Tourist Village constituted a Governor’s attempt in packaging tourism, so that foreign tourists would like to come. Through the rule, Ida Wahyuni Sahabudin, a community development activist, took an innitiative to promote Setanggor Village as one of destinations of Halal Tourist Village. He improved various local assets into attractive tourist spots. This study described the roles of community assets in developing community of Halal Tourist Village of Setanggor. This study used library research method and a concept approach of community assets. The result of this study indicated that that those various assets came with different roles and all of them were integrated in the tourism of Setanggor Village to overcome the poverty problem there.